Climate-mediated dynamics of the northern limit of paddy rice in China - Liang, Shefang; Wu, Wenbin; Sun, Jing; Li, Zhipeng; Sun, Xiao; Chen, Hao; Chen, Shi; Fan, Lingling; You, Liangzhi; Yang, Peng (IOP Publishing, 2021)
Paddy rice agriculture plays an important role in food security and has a considerable influence on natural systems. In the context of climate change, understanding the nature and drivers of shifts in the northern limit of paddy rice (NLPR) is crucial for adaptation strategies and food security. However, quantitative studies on the effect of climate change on paddy rice distribution shifts have not been well performed. Here, we mapped the NLPR in China using Landsat imagery from 1984 to 2013, analyzed the latitudinal and elevational dynamics of the NLPR using Fishnet analysis, and explored the factors driving the changes in rice area across the NLPR regions using a linear regression model. Our results show that between 1984 and 2013, the NLPR shifted 24.93 km northward (the greatest movement was 88.01 km occurring at approximately 133° E) and elevational limits increased by 39.15 m (the greatest movement was 117.08 m occurring at approximately 129° E). While socioeconomic factors (e.g. benefits, policies, irrigation, and mulch) played significant roles in rice area changes, the changes in rice area across the NLPR regions had the strongest positive association with the increase in the previous temperature, indicating that rice cultivation in the NLPR regions has moved to higher latitudes over the 30 year study period to adapt to climate change. Our study highlighted that quantifying the interactions between climate change and crop production systems can facilitate a better understanding of the human responses to changes in the growing conditions in the face of climate change and ensuring regional and global food security.